Comparison of clinical outcomes in patients with congenital anorectal malformation treated with posterior sagittal anorectoplasty and laparoscopically assisted anorectal pull through - Kunnur, Vijaymahantesh S; Singh, Chandra Shekhar; Kunnur, Shanthala V; Kunnur, Anil Kumar S (Indian Journal of Child Health, 2016)
Aim: To compare the complications and outcomes of laparoscopic-assisted anorectoplasty (LAARP) for anorectal malformation (ARM) with that of posterior sagittal anorectoplasty (PSARP) using Kelly’s score. Materials and Methods: This was a single-center study conducted over a period of 4-year. A total of 95 male ARM patients were included in the study, of which 25 patients underwent LAARP, whereas 70 patients underwent PSARP. Result: Superficial wound infection was seen in 2 (2.85%) cases of the PSARP group while in 1 (4%) case in LAARP group. 12 (17.14%) cases of PSARP group had wound dehiscence at the neo-anal site, of which 6 (8.57%) had complete wound dehiscence and the remaining 6 (8.57%) had partial dehiscence, whereas 4 (16%) cases had wounddehiscence in LAARP group of which 3 (12%) had partial and 1 (4%) had complete dehiscence. Retraction of the neo-anus was seen in 6 (8.57%) cases of PSARP group while in 2 (8%) cases of LAARP group. Ectopically placed neo-anus was seen in 3 (4.28%) patients of PSARP group while in none of the cases in LAARP group. None of the patients in LAARP group had anal stenosis, whereas 2 (2.85%) patients underwent redoanoplasty in PSARP group for anal stenosis. Mucosal prolapse was seen in 8 (11.42%) cases of PSARP group, as compared to 3 (12%) patients of LAARP group. The net average Kelly’s score in LAARP group was 4.56, whereas, in PSARP group, it was 4.10. Conclusion: This study emphasizes the emerging laparoscopic technique for the managementof ARMs. Using this approach, it is possible to achieve better continence rates as the extent of perineal dissection is minimal.